PEMBENTUKAN ANTI-AUTOMORFISMA PADA GELANGGANG OPERATOR DIFERENSIAL - Amir, Amir Kamal (MATEMATIKA, 2011)
﻿﻿. Let  R be any ring with identity 1,  be an endomorphism of  R and  be a left -derivation. The skew polynomial  ring over R in an indeterminate x, denoted by  , is the set of    polynomials  where  with  multiplication rule  for all  For    the skew polynomial ring is written as  and is called differential operator ring. In this paper will be constructed  anti-automorphism on this ring, i.e., .